The use of Māori words in National Science Challenge online discourse. Issue 4 (1st October 2020) - Calude, Andreea; Stevenson, Louise; Whaanga, Hēmi; Keegan, Te Taka
ABSTRACT: New Zealand English is well-known for its heavy borrowing of words from Māori. This lexical component, unique to New Zealand English alone has been studied intensely over the last 50 years, particularly in newspaper media. Current research suggests the use is still increasing today, primarily in Māori-related contexts. Here, we analyse a surprising and unexpected use of Māori loanwords in science digital discourse (neither genre being previously investigated), where we discover a strong presence of Māori borrowings in National Science Challenge website and Twitter content. Using corpus linguistics methods, we argue that the use of Māori loanwords in this genre functions as a national identity building tool, used by various authors to signal that the 'challenges' the country faces are uniquely New Zealand's 'challenges'.